Epidemiology of Perceived Spiritual ATM Card Swapping Scams in Makurdi, Nigeria: Victim Narratives (Abuja Journal of Sociological Studies, 2026)
ATM card swapping is a distraction-based fraud in which perpetrators exchange victims' genuine cards while capturing PINs. In Makurdi, Nigeria, this scam is frequently attributed to spiritual manipulation (juju or hypnosis-like disorientation), contributing to severe underreporting. This qualitative study examined the phenomenon through semi-structured interviews with 35 key informants (20 victims, 5 bank officials, 5 police officers, 5 EFCC officials) recruited via purposive and snowball sampling. Thematic analysis using NVivo identified four core themes: (1) exploitation of technical ATM failures through distraction, (2) widespread perception of spiritual influence among victims, (3) delayed or avoided reporting due to stigma and fear of supernatural retaliation, and (4) institutional barriers including slow account blocking and lack of CCTV. Relevance Theory (Sperber & Wilson, 1995) explains how culturally salient juju assumptions enable fraudsters to bypass vigilance and later rationalise victim silence. Findings highlight the need for culturally tailored awareness campaigns, instant remote-blocking tools, mandatory CCTV, and community-based reporting channels to break the cycle of vulnerability in spiritually framed financial crime.